1999
DOI: 10.1016/s0014-5793(99)01131-x
|View full text |Cite
|
Sign up to set email alerts
|

Differential down‐regulation of CD95 or CD95L in chronically HIV‐infected cells of monocytic or lymphocytic origin: cellular studies and molecular analysis by quantitative competitive RT‐PCR

Abstract: We analysed the expression of CD95/CD95L in two widely used models for studying the cellular effects of chronic infection with human immunodeficiency virus type 1 (HIV-1), i.e. ACH-2 cells, derived from the lymphocytic cell line A301, and U1, derived from monocytic U937 cells. A301 and ACH-2 mounted the same amount of plasma membrane CD95, while U1 had a consistent decrease in CD95 expression. Using different antibodies, we failed to detect the plasma membrane form of its ligand, CD95L, but we could see the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 49 publications
1
18
0
Order By: Relevance
“…Because it is 20 bp shorter, it can be easily distinguished from wild-type DNA on agarose gel. This fragment was cloned into the pFASL plasmid that contains the competitor for CD95L [28], taking advantage of the consensus sequences for Eco RI and Xba I restriction enzymes present at both ends. The construct, named pMito, was extracted from Escherichia coli cells by use of a High Pure plasmid isolation kit, was quantified by spectrophotometer and limiting dilution analysis, and was stored at 220 C. This construct was used with QC-PCR to evaluate the number of copies of mtDNA or genomic DNA (gDNA) that are present in a sample, depending on the primers used in the PCR mix.…”
Section: Methodsmentioning
confidence: 99%
“…Because it is 20 bp shorter, it can be easily distinguished from wild-type DNA on agarose gel. This fragment was cloned into the pFASL plasmid that contains the competitor for CD95L [28], taking advantage of the consensus sequences for Eco RI and Xba I restriction enzymes present at both ends. The construct, named pMito, was extracted from Escherichia coli cells by use of a High Pure plasmid isolation kit, was quantified by spectrophotometer and limiting dilution analysis, and was stored at 220 C. This construct was used with QC-PCR to evaluate the number of copies of mtDNA or genomic DNA (gDNA) that are present in a sample, depending on the primers used in the PCR mix.…”
Section: Methodsmentioning
confidence: 99%
“…Regarding the housing conditions, we recently demonstrated involvement of the Fas/FasL pathway in resistance to BM grafts and that diminished BM rejection capacity during conventional housing conditions may be explained by down-regulation of NK cell FasL expression (21). This down-regulation could be induced by pathogens infecting the animals (22), since sentinel mice in our conventional animal facility occasionally carry viral infections, e.g., mouse hepatitis virus, mouse parvovirus, and sendai virus. In addition, the inhibitor cellular FLIP, overexpressed in susceptible hemopoietic stem cells, was shown to convey partial engraftment in B6 PKO mice, suggesting involvement of death receptors in BM rejection (23).…”
Section: N Atural Killer Cells Are the Primary Effector Cells Mediatimentioning
confidence: 95%
“…One explanation for the low levels of FasL on NK cells from mice housed in a conv colony is viral infections. Studies with lymphocytic cell lines have shown that FasL expression is down-regulated upon infection with HIV [23]. Interestingly, mice living in our conv colony have been diagnosed with several viral infections, such as mouse hepatitis virus and Sendai virus.…”
Section: Discussionmentioning
confidence: 99%